Olefin-based polymers and methods of making same

The olefin-based polymer prepared by a mixed catalyst system and a slurry polymerization method solves the problems of insufficient processability and heat-sealing properties in the existing technology, achieves a wide molecular weight distribution and a short-chain branching structure, and improves the mechanical strength and heat-sealing performance of the film.

CN120682405APending Publication Date: 2025-09-23HANWHA SOLUTIONS CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510858097.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2020-12-17
Filing Date
2021-12-10
Publication Date
2025-09-23

AI Technical Summary

Technical Problem

Existing linear low-density polyethylene films prepared based on metallocene catalysts have problems with poor processability and reduced heat-sealing properties, making it difficult to simultaneously possess excellent mechanical strength and heat-sealing properties.

Method used

A mixed catalyst system comprising first and second transition metal compounds of specific chemical formulae is used to prepare olefin-based polymers by a slurry polymerization process, wherein the density, melt index ratio and comonomer distribution slope of the polymers are controlled to obtain a broad molecular weight distribution and a short-chain branching structure.

Benefits of technology

It achieves excellent processability and mechanical strength based on olefin polymers, improves the heat sealing properties of the film, and meets the needs of high mechanical strength and heat sealing performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120682405A_ABST
    Figure CN120682405A_ABST
Patent Text Reader

Abstract

The present invention relates to olefin-based polymers and methods of making the same. The olefin-based polymer according to one embodiment of the present invention has a wide molecular weight distribution, and thus has excellent processability. In addition, there is a relatively large number of short chain branches in the high molecular weight component of the olefin-based polymer, and thus the olefin-based polymer has excellent mechanical strength and heat sealing properties.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the Chinese patent application with the application date of December 10, 2021, application number "202180090148.7", and invention name "Olefin-based polymers and preparation methods thereof". The original application is the Chinese national phase application of international application PCT / KR2021 / 018720. Technical Field

[0002] The present invention relates to an olefin-based polymer and a method for preparing the same. In particular, the present invention relates to an olefin-based polymer having excellent mechanical strength and a method for preparing the same. Background Art

[0003] A metallocene catalyst has a sandwich structure as a basic form, which is one of catalysts used for olefin polymerization and is a compound in which a ligand such as a cyclopentadienyl group, an indenyl group, or a cycloheptadienyl group is coordinated with a transition metal compound or a transition metal halogen compound.

[0004] Ziegler-Natta catalysts, another type of catalyst used to polymerize olefins, have heterogeneous active sites because the metal components serving as active sites are dispersed on an inert solid surface. Metallocene catalysts, however, are considered single-site catalysts with uniform polymerization properties across all active sites because they are compounds with a specific structure. Polymers polymerized using metallocene catalysts like these have narrow molecular weight distributions, uniform comonomer distributions, and copolymerization activities higher than those of Ziegler-Natta catalysts.

[0005] Meanwhile, linear low-density polyethylene (LLDPE) is produced by copolymerizing ethylene and α-olefins using a polymerization catalyst under low pressure, and has a narrow molecular weight distribution and short chain branches (SCB) of a certain length, and generally does not have long chain branches (LCB). Films produced using linear low-density polyethylene have high breaking strength and elongation, as well as excellent tear strength, impact strength, and other general properties of polyethylene, and are therefore widely used in stretch films, overlapping films, and the like, which are difficult to apply to conventional low-density polyethylene or high-density polyethylene.

[0006] However, linear low-density polyethylene produced by a metallocene catalyst has poor processability due to a narrow molecular weight distribution, and films produced therefrom tend to have reduced heat-sealing properties.

[0007] Therefore, there is a need for olefin-based polymers that allow for the preparation of films having excellent mechanical strength and heat-sealing properties while having excellent processability. Summary of the Invention

[0008] Technical issues

[0009] An object of the present invention is to provide an olefin-based polymer that allows the preparation of an olefin-based polymer film having excellent mechanical strength and heat-sealing properties while having excellent processability.

[0010] Another object of the present invention is to provide a process for preparing olefin-based polymers.

[0011] Technical Solution

[0012] In one general aspect, an olefin-based polymer having (1) 0.915 g / cm 3 to 0.935g / cm 3 , preferably 0.918 g / cm 3 to 0.932g / cm 3 (2) 15 or more, preferably 15 to 40 at 190 ℃ at a load of 21.6kg measured melt index (I 21.6 ) and the melt index (I 2.16 ) ratio (melt flow ratio; meltflow ratio, MFR); and (3) 1.0 or greater, preferably 1.0 to 3.0, a comonomer distribution slope (CDS) defined by the following formula 1:

[0013] [Formula 1]

[0014]

[0015] Among them C 20 and C 80 is the comonomer content at the points where the cumulative weight fractions in the comonomer distribution are 20% and 80%, respectively, and M 20 and M 80 are the molecular weights at the points in the comonomer distribution where the cumulative weight fractions are 20% and 80%, respectively.

[0016] In one specific example of the present invention, the olefin-based polymer may be prepared by polymerizing an olefin-based monomer in the presence of a mixed catalyst comprising: at least one first transition metal compound represented by the following Chemical Formula 1; and at least one second transition metal compound represented by the following Chemical Formula 2:

[0017] [Chemical Formula 1]

[0018]

[0019] [Chemical Formula 2]

[0020]

[0021] wherein n is independently an integer from 1 to 20,

[0022] M is independently titanium (Ti), zirconium (Zr), or hafnium (Hf),

[0023] X is independently halogen, C 1-20 Alkyl, C 2-20 Alkenyl, C 2-20 Alkynyl, C 6-20 Aryl, C 1-20 Alkyl C 6-20 Aryl, C 6-20 Aryl C 1-20 Alkyl, C 1-20 Alkylamide, or C 6-20 Arylamide group,

[0024] R1 to R8 are independently hydrogen, substituted or unsubstituted C 1-20 Alkyl, substituted or unsubstituted C 2-20 Alkenyl, substituted or unsubstituted C 6-20 Aryl, substituted or unsubstituted C 1-20 Alkyl C 6-20 Aryl, substituted or unsubstituted C 6-20 Aryl C 1-20 Alkyl, substituted or unsubstituted C 1-20 Heteroalkyl, substituted or unsubstituted C 3-20 Heteroaryl, substituted or unsubstituted C 1-20 Alkylamide, substituted or unsubstituted C 6-20 Arylamide, substituted or unsubstituted C 1-20 Alkylene, or substituted or unsubstituted C 1-20 Silyl, and

[0025] R9 to R 11 and R 12 to R 14 are independently substituted or unsubstituted C 1-20 Alkyl, substituted or unsubstituted C 2-20 Alkenyl, substituted or unsubstituted C 6-20 Aryl, substituted or unsubstituted C 1-20 Alkyl C 6-20 Aryl, substituted or unsubstituted C 6-20 Aryl C 1-20 Alkyl, substituted or unsubstituted C 1-20 Heteroalkyl, substituted or unsubstituted C3-20 Heteroaryl, substituted or unsubstituted C 1-20 Alkylamide, substituted or unsubstituted C 6-20 Arylamide, substituted or unsubstituted C 1-20 Alkylene, or substituted or unsubstituted C 1-20 Silyl, but

[0026] R1 to R8 can be independently connected to adjacent groups to form a substituted or unsubstituted saturated or unsaturated C 4-20 ring.

[0027] In a specific embodiment of the present invention, M can be zirconium or hafnium, and X can be halogen or C 1-20 Alkyl, R1 to R8 can be hydrogen, substituted or unsubstituted C 1-20 Alkyl, substituted or unsubstituted C 1-20 alkenyl, or substituted or unsubstituted C 6-20 Aryl, and R9 to R 11 and R 12 to R 14 C may be substituted or unsubstituted 1-20 alkyl.

[0028] In a preferred embodiment of the present invention, the first transition metal compound may be at least one of the transition metal compounds represented by the following Chemical Formulas 1-1 to 1-3, and the second transition metal compound may be a transition metal compound represented by the following Chemical Formula 2-1:

[0029] [Chemical Formula 1-1] [Chemical Formula 1-2] [Chemical Formula 1-3]

[0030]

[0031] [Chemical Formula 2-1]

[0032]

[0033] Wherein Me is methyl.

[0034] In one embodiment of the present invention, the molar ratio of the first transition metal compound to the second transition metal compound is in the range of 100:1 to 1:100.

[0035] In one embodiment of the present invention, the catalyst may include at least one co-catalyst selected from the group consisting of a compound represented by the following Chemical Formula 3, a compound represented by the following Chemical Formula 4, and a compound represented by the following Chemical Formula 5:

[0036] [Chemical Formula 3]

[0037]

[0038] [Chemical Formula 4]

[0039]

[0040] [Chemical Formula 5]

[0041] [LH] + [Z(A)4] - or [L] + [Z(A)4] -

[0042] Where n is an integer of 2 or greater, R a Halogen atoms, C 1-20 Hydrocarbon, or halogen-substituted C 1-20 Hydrocarbon group,

[0043] D is aluminum (Al) or boron (B), R b 、R c and R d are independently halogen atoms, C 1-20 Hydrocarbon, halogen-substituted C 1-20 Hydrocarbon, or C 1-20 Alkoxy,

[0044] L is a neutral Lewis base or a cationic Lewis base, [LH] + and [L] + is a Bronsted acid, Z is a Group 13 element, and A is independently substituted or unsubstituted C 6-20 Aryl or substituted or unsubstituted C 1-20 alkyl.

[0045] In one embodiment of the present invention, the catalyst may further comprise a carrier supporting the transition metal compound, the co-catalyst compound, or both.

[0046] In a preferred embodiment of the present invention, the support may include at least one selected from the group consisting of silica, alumina, and magnesia.

[0047] Herein, the total amount of the mixed transition metal compound supported on the carrier may be 0.001 to 1 mmol based on 1 g of the carrier, and the total amount of the co-catalyst compound supported on the carrier may be 2 to 15 mmol based on 1 g of the carrier.

[0048] In one embodiment of the present invention, the olefin-based polymer may be a copolymer of an olefin-based monomer and an olefin-based comonomer. Specifically, the olefin-based monomer may be ethylene, and the olefin-based comonomer may be at least one selected from the group consisting of propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, and 1-hexadecene. Preferably, the olefin-based polymer may be a linear low-density polyethylene in which the olefin-based polymer is ethylene and the olefin-based monomer is 1-hexene.

[0049] In another general aspect, a method for preparing an olefin-based polymer comprises: polymerizing an olefin-based monomer in the presence of a mixed catalyst, thereby obtaining an olefin-based polymer, the mixed catalyst comprising: at least one first transition metal compound represented by Chemical Formula 1; and at least one second transition metal compound represented by Chemical Formula 2, wherein the olefin-based polymer has (1) 0.915 g / cm 3 to 0.935g / cm 3 , preferably 0.918 g / cm 3 to 0.932g / cm 3 (2) 15 or more, preferably 15 to 40 at 190 ℃ at a load of 21.6kg measured melt index (I 21.6 ) and the melt index (I 2.16 ) ratio (melt flow ratio; MFR); and (3) a comonomer distribution slope (CDS) defined by Formula 1 of 1.0 or greater, preferably 1.0 to 3.0.

[0050] In one specific example of the present invention, the polymerization of the olefin-based monomer may be performed by slurry polymerization, and specifically, the polymerization of the olefin-based monomer may be performed in a slurry batch reactor.

[0051] Beneficial effects

[0052] The olefin-based polymer according to an exemplary embodiment of the present invention has a broad molecular weight distribution and thus has excellent processability. In addition, a relatively large amount of short chain branches are present in the high molecular weight component of the olefin-based polymer, so the olefin-based polymer has excellent mechanical strength and heat sealing properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] Figure 1 is a GPC-FTIR chart for describing the method for measuring CDS defined by Formula 1.

[0054] Figures 2 to 9These are GPC-FTIR charts for measuring CDS of the olefin-based polymers of Examples 1 to 8, respectively.

[0055] Figure 10 and 11 These are GPC-FTIR charts for measuring CDS of the olefin-based polymers of Comparative Examples 1 and 2, respectively. DETAILED DESCRIPTION

[0056] Hereinafter, the present invention will be described in more detail.

[0057] Olefin-based polymers

[0058] According to an exemplary embodiment of the present invention, there is provided an olefin-based polymer having (1) 0.915 g / cm 3 to 0.935g / cm 3 (2) a melt index (I) of 15 or greater measured at 190°C under a load of 21.6 kg 21.6 ) and the melt index (I 2.16 ) ratio (melt flow ratio; MFR); and (3) a comonomer distribution slope (CDS) defined by Formula 1 of 1.0 or greater.

[0059] In one embodiment of the present invention, the density of the olefin-based polymer is 0.915 g / cm 3 to 0.935g / cm 3 Preferably, the density of the olefin-based polymer may be 0.918 g / cm 3 to 0.932g / cm 3 .

[0060] In one embodiment of the present invention, the melt index (I) of the olefin-based polymer measured at 190° C. under a load of 21.6 kg is 21.6 ) and the melt index (I 2.16 ) ratio (melt flow ratio; MFR) may be 15 or more. Preferably, the MFR of the olefin-based polymer may be 15 to 40.

[0061] In one embodiment of the present invention, the comonomer distribution slope (CDS) of the olefin-based polymer, as defined by the following Formula 1, may be 1.0 or greater. Preferably, the CDS of the olefin-based polymer may be 1.0 to 3.0.

[0062] [Formula 1]

[0063]

[0064] Among them C20 and C 80 is the comonomer content at the points where the cumulative weight fractions in the comonomer distribution are 20% and 80%, respectively, and M 20 and M 80 are the molecular weights at the points in the comonomer distribution where the cumulative weight fractions are 20% and 80%, respectively.

[0065] The CDS of an olefin-based polymer represents the slope of the comonomer content relative to the molecular weight at points where the cumulative weight fraction is 20% and 80%, respectively, on a comonomer distribution graph. Since the CDS of an olefin-based polymer is high, the copolymer is concentrated in polymer chains with higher molecular weights, resulting in superior mechanical strength and heat-sealing properties.

[0066] Herein, the comonomer distribution of an olefin-based polymer can be measured continuously with the molecular weight and molecular weight distribution of the polymer using a GPC-FTIR device.

[0067] It is understood that since the olefin-based polymer according to an exemplary embodiment of the present invention has a relatively large molecular weight distribution and has more short-chain branches in the high-molecular weight component, the mechanical strength and heat-sealing properties of the olefin-based polymer film manufactured therefrom are excellent.

[0068] In one specific example of the present invention, the olefin-based polymer may be prepared by polymerizing an olefin-based monomer in the presence of a mixed catalyst comprising: at least one first transition metal compound represented by the following Chemical Formula 1; and at least one second transition metal compound represented by the following Chemical Formula 2:

[0069] [Chemical Formula 1]

[0070]

[0071] [Chemical Formula 2]

[0072]

[0073] wherein n is independently an integer from 1 to 20, preferably an integer from 1 to 10, and more specifically an integer from 1 to 5. Specifically, n may be 1 or 2, respectively.

[0074] M is independently titanium (Ti), zirconium (Zr), or hafnium (Hf). Specifically, M can be zirconium or hafnium.

[0075] X is independently halogen, C 1-20 Alkyl, C 2-20 Alkenyl, C 2-20 Alkynyl, C 6-20 Aryl, C1-20 Alkyl C 6-20 Aryl, C 6-20 Aryl C 1-20 Alkyl, C 1-20 Alkylamide, or C 6-20 Arylamide, specifically, X can be halogen or C 1-20 Preferably, X can be chlorine or methyl.

[0076] R1 to R8 are independently hydrogen, substituted or unsubstituted C 1-20 Alkyl, substituted or unsubstituted C 2-20 Alkenyl, substituted or unsubstituted C 6-20 Aryl, substituted or unsubstituted C 1-20 Alkyl C 6-20 Aryl, substituted or unsubstituted C 6-20 Aryl C 1-20 Alkyl, substituted or unsubstituted C 1-20 Heteroalkyl, substituted or unsubstituted C 3-20 Heteroaryl, substituted or unsubstituted C 1-20 Alkylamide, substituted or unsubstituted C 6-20 Arylamide, substituted or unsubstituted C 1-20 Alkylene, or substituted or unsubstituted C 1-20 Silyl, wherein R1 to R8 can be independently connected to adjacent groups to form a substituted or unsubstituted saturated or unsaturated C 4-20 Specifically, R1 to R8 can be hydrogen, substituted or unsubstituted C 1-20 Alkyl, substituted or unsubstituted C 1-20 Alkenyl, or substituted or unsubstituted C 6-20 Aryl.

[0077] R9 to R 11 and R 12 to R 14 are independently substituted or unsubstituted C 1-20 Alkyl, substituted or unsubstituted C 2-20 Alkenyl, substituted or unsubstituted C 6-20 Aryl, substituted or unsubstituted C 1-20 Alkyl C 6-20 Aryl, substituted or unsubstituted C 6-20 Aryl C 1-20 Alkyl, substituted or unsubstituted C 1-20 Heteroalkyl, substituted or unsubstituted C 3-20 Heteroaryl, substituted or unsubstituted C 1-20Alkylamide, substituted or unsubstituted C 6-20 Arylamide, substituted or unsubstituted C 1-20 Alkylene, or substituted or unsubstituted C 1-20 Silyl. Specifically, R9 to R 11 and R 12 to R 14 may be independently substituted or unsubstituted C 1-20 Alkyl or substituted or unsubstituted C 6-20 Preferably, R9 to R 11 and R 12 to R 14 They may be methyl groups.

[0078] In a specific embodiment of the present invention, M can be zirconium or hafnium, and X can be halogen or C 1-20 Alkyl, R1 to R8 can be hydrogen, substituted or unsubstituted C 1-20 Alkyl, substituted or unsubstituted C 1-20 alkenyl, or substituted or unsubstituted C 6-20 Aryl, and R9 to R 11 and R 12 to R 14 C may be substituted or unsubstituted 1-20 alkyl.

[0079] In a preferred embodiment of the present invention, the first transition metal compound may be at least one of the transition metal compounds represented by the following Chemical Formulas 1-1 to 1-3, and the second transition metal compound may be a transition metal compound represented by the following Chemical Formula 2-1:

[0080] [Chemical Formula 1-1] [Chemical Formula 1-2] [Chemical Formula 1-3]

[0081]

[0082] [Chemical Formula 2-1]

[0083]

[0084] Wherein Me is methyl.

[0085] In a specific embodiment of the present invention, the molar ratio of the first transition metal compound to the second transition metal compound is in the range of 100:1 to 1:100. Preferably, the molar ratio of the first transition metal compound to the second transition metal compound is in the range of 50:1 to 1:50. Preferably, the molar ratio of the first transition metal compound to the second transition metal compound is in the range of 10:1 to 1:10.

[0086] In one embodiment of the present invention, the catalyst may include at least one co-catalyst compound selected from the group consisting of a compound represented by the following Chemical Formula 3, a compound represented by the following Chemical Formula 4, and a compound represented by the following Chemical Formula 5:

[0087] [Chemical Formula 3]

[0088]

[0089] Where n is an integer of 2 or greater, R a Halogen atoms, C 1-20 Hydrocarbon, or halogen-substituted C 1-20 hydrocarbons, and specifically, R a It can be methyl, ethyl, n-butyl, or isobutyl,

[0090] [Chemical Formula 4]

[0091]

[0092] Where D is aluminum (Al) or boron (B), and R b 、R c and R d are independently halogen atoms, C 1-20 Hydrocarbon, halogen-substituted C 1-20 Hydrocarbon, or C 1-20 Alkoxy, and specifically, when D is aluminum (Al), R b 、R c and R d may be independently methyl or isobutyl, and when D is boron (B), R b 、R c and R d They can be pentafluorophenyl,

[0093] [Chemical Formula 5]

[0094] [LH] + [Z(A)4] - or [L] + [Z(A)4] -

[0095] Where L is a neutral Lewis base or a cationic Lewis base, [LH] + and [L] + is a Bronsted acid, Z is a Group 13 element, and A is independently substituted or unsubstituted C 6-20 Aryl or substituted or unsubstituted C 1-20 Alkyl, and specifically, [LH] + Dimethylaniline Cation, [Z(A)4] - It can be [B(C6F5)4] - , and [L] + It can be [(C6H5)3C] + .

[0096] Specifically, examples of the compound represented by Chemical Formula 3 include methylaluminoxane, ethylaluminoxane, isobutylaluminoxane, butylaluminoxane, and the like, and preferably methylaluminoxane, but is not limited thereto.

[0097] Examples of the compound represented by Chemical Formula 4 include trimethylaluminum, triethylaluminum, triisobutylaluminum, tripropylaluminum, tributylaluminum, dimethylaluminum chloride, triisopropylaluminum, tri-sec-butylaluminum, tricyclopentylaluminum, tripentylaluminum, triisopentylaluminum, trihexylaluminum, trioctylaluminum, ethyldimethylaluminum, methyldiethylaluminum, triphenylaluminum, tri-p-tolylaluminum, dimethylaluminum methoxide, dimethylaluminum ethoxide, trimethylboron, triethylboron, triisobutylboron, tripropylboron, tributylboron, and the like, and preferably trimethylaluminum, triethylaluminum, and triisobutylaluminum, but not limited thereto.

[0098] Examples of the compound represented by Chemical Formula 5 include triethylammonium tetraphenylboron, tributylammonium tetraphenylboron, trimethylammonium tetraphenylboron, tripropylammonium tetraphenylboron, trimethylammonium tetra(p-tolyl)boron, trimethylammonium tetra(o,p-dimethylphenyl)boron, tributylammonium tetra(p-trifluoromethylphenyl)boron, trimethylammonium tetra(p-trifluoromethylphenyl)boron, tributylammonium tetra(pentafluorophenyl)boron, N,N-diethylaniline Tetraphenylboron, N,N-diethylaniline Tetrakispentafluorophenylborane, diethylammonium tetrakispentafluorophenylborane, triphenyl Tetraphenylborane, trimethyl Tetraphenylboron, triethylammonium tetraphenylaluminum, tributylammonium tetraphenylaluminum, trimethylammonium tetraphenylaluminum, tripropylammonium tetraphenylaluminum, trimethylammonium tetra(p-tolyl)aluminum, tripropylammonium tetra(p-tolyl)aluminum, triethylammonium tetra(o,p-dimethylphenyl)aluminum, tributylammonium tetra(p-trifluoromethylphenyl)aluminum, trimethylammonium tetra(p-trifluoromethylphenyl)aluminum, tributylammonium tetrapentafluorophenylaluminum, N,N-diethylaniline Tetraphenylaluminum, N,N-diethylaniline Tetrafluorophenylaluminum, diethylammonium tetrapentafluorophenylaluminum, triphenyl Tetraphenylaluminum, trimethyl Tetraphenylaluminum, tripropylammonium tetra(p-tolyl)boron, triethylammonium tetra(o,p-dimethylphenyl)boron, tributylammonium tetra(p-trifluoromethylphenyl)boron, triphenylcarbon Tetrakis(p-trifluoromethylphenyl)boron, triphenylcarbon Tetrakispentafluorophenylborane, etc.

[0099] In a specific embodiment of the present invention, the catalyst may further comprise a carrier supporting a transition metal compound, a co-catalyst compound, or both. Specifically, the carrier may support both a transition metal compound and a co-catalyst compound.

[0100] In this article, the carrier may be included in a material containing a hydroxyl group on the surface, and preferably, a material with a highly reactive hydroxyl group and a siloxane group that is dried to remove moisture from the surface can be used. For example, the carrier may include at least one selected from silica, alumina, and magnesium oxide. Specifically, silica, silica-alumina, silica-magnesium oxide, etc. dried at high temperatures can be used as carriers, and these can generally include oxides, carbonates, sulfates, and nitrate components, such as Na2O, K2CO3, BaSO4, and Mg(NO3)2. In addition, these can include carbon, zeolite, magnesium chloride, etc. However, the carrier is not limited thereto, and is not particularly limited, as long as it can load transition metal compounds and co-catalyst compounds.

[0101] The average particle size of the carrier may be 10 μm to 250 μm, preferably 10 μm to 150 μm, and more preferably 20 μm to 100 μm.

[0102] The micropore volume of the support may be from 0.1 cc / g to 10 cc / g, preferably from 0.5 cc / g to 5 cc / g, and more preferably from 1.0 cc / g to 3.0 cc / g.

[0103] The specific surface area of ​​the carrier can be 1m 2 / g to 1,000m 2 / g, preferably 100m 2 / g to 800m 2 / g, and more preferably 200m 2 / g to 600m 2 / g.

[0104] In a preferred embodiment of the present invention, the support may be silica. Herein, the silica may be dried at a temperature of 200°C to 900°C. The drying temperature may be 300°C to 800°C, and more preferably 400°C to 700°C. When the drying temperature is below 200°C, the silica contains too much moisture, causing the moisture on the surface to react with the co-catalyst compound. When the drying temperature is above 900°C, the support structure may collapse.

[0105] The concentration of hydroxyl groups in the dried silica may be 0.1 mmol / g to 5 mmol / g, preferably 0.7 mmol / g to 4 mmol / g, and more preferably 1.0 mmol / g to 2 mmol / g. When the concentration of hydroxyl groups is less than 0.1 mmol / g, the loading amount of the first co-catalyst compound is reduced, and when the concentration is greater than 5 mmol / g, the catalyst component becomes inactive.

[0106] The total amount of the transition metal compound supported on the carrier can be 0.001 mmol to 1 mmol based on 1 g of the carrier. When the ratio of the transition metal compound to the carrier satisfies the above range, appropriate supported catalyst activity is exhibited, which is advantageous in terms of catalyst activity retention and economic feasibility.

[0107] The total amount of the promoter compound supported on the carrier may be 2 mmol to 15 mmol based on 1 g of the carrier. When the ratio of the promoter compound to the carrier satisfies the above range, it is advantageous in terms of catalyst activity maintenance and economic feasibility.

[0108] The carrier may be one or two or more. For example, both the transition metal compound and the co-catalyst compound may be supported on one carrier, or each of the transition metal compound and the co-catalyst compound may be supported on two or more carriers. In addition, only one of the transition metal compound and the co-catalyst compound may be supported on a carrier.

[0109] As a method for supporting the transition metal compound and / or the co-catalyst compound in the catalyst that can be used for olefin polymerization, a physical adsorption method or a chemical adsorption method can be used.

[0110] For example, the physical adsorption method may be a method comprising bringing a solution in which a transition metal compound is dissolved into contact with a support and then drying; a method comprising bringing a solution in which a transition metal compound and a co-catalyst compound are dissolved into contact with a support and then drying; a method comprising bringing a solution in which a transition metal compound is dissolved into contact with a support and then drying to prepare a support on which the transition metal compound is loaded, separately bringing a solution in which a co-catalyst compound is dissolved into contact with a support and then drying to prepare a support on which the co-catalyst compound is loaded, and then mixing them; and the like.

[0111] The chemical adsorption method may be a method comprising first loading a co-catalyst compound on the surface of a support and then loading a transition metal compound on the co-catalyst compound; or a method comprising covalently bonding a functional group on the surface of the support (for example, a hydroxyl group (-OH) on the surface of silica in the case of silica) and a catalyst compound.

[0112] In one embodiment of the present invention, the olefin-based polymer may be a homopolymer of an olefin-based monomer or a copolymer of an olefin-based monomer and a comonomer. Preferably, the olefin-based polymer is a copolymer of an olefin-based monomer and an olefin-based comonomer.

[0113] In this context, the olefin-based monomer may be selected from C 2-20 α-olefins, C 1-20 Diolefins, C 3-20 Cycloolefins and C 3-20 At least one of the cycloalkadienes.

[0114] For example, the olefin-based monomer may be ethylene, propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, or 1-hexadecene, and the olefin-based polymer may be a homopolymer containing only one of the above-exemplified olefin-based monomers or a copolymer containing two or more of the above-exemplified olefin-based monomers.

[0115] In an exemplary embodiment, the olefin-based polymer may be ethylene and C 3-20 Copolymer of α-olefin. Preferably, the olefin-based polymer may be a linear low-density polyethylene in which the olefin-based monomer is ethylene and the olefin-based comonomer is 1-hexene.

[0116] In this case, the content of ethylene is preferably 55% to 99.9% by weight, and more preferably 90% to 99.9% by weight. The content of the α-olefin-based comonomer is preferably 0.1% to 45% by weight, and more preferably 0.1% to 10% by weight.

[0117] Process for preparing olefin-based polymers

[0118] According to an exemplary embodiment of the present invention, a method for preparing an olefin-based polymer is provided, comprising: polymerizing an olefin-based monomer in the presence of a mixed catalyst, thereby obtaining an olefin-based polymer, the mixed catalyst comprising: at least one first transition metal compound represented by the following Chemical Formula 1; and at least one second transition metal compound represented by the following Chemical Formula 2:

[0119] [Chemical Formula 1]

[0120]

[0121] [Chemical Formula 2]

[0122]

[0123] Where n, M, X, R1 to R8 and R9 to R 14 As defined above in the heading "Olefin-based polymers".

[0124] As described above, the olefin-based polymer prepared by the preparation method according to an exemplary embodiment of the present invention may have (1) 0.915 g / cm 3 to 0.935g / cm 3 , preferably 0.918 g / cm 3 to 0.932g / cm 3 (2) 15 or more, preferably 15 to 40 at 190 ℃ at a load of 21.6kg measured melt index (I 21.6 ) and the melt index (I 2.16 ) ratio (melt flow ratio; MFR); and (3) a comonomer distribution slope (CDS) defined by the following formula 1 of 1.0 or greater, preferably 1.0 to 3.0:

[0125] [Formula 1]

[0126]

[0127] Among them C 20 、C 80 、M 20 and M 80 As defined above in the heading "Olefin-based polymers".

[0128] In a specific example of the present invention, the olefin-based polymer may be polymerized through polymerization reactions such as radical polymerization, cationic polymerization, coordination polymerization, condensation polymerization, and addition polymerization, but is not limited thereto.

[0129] In an exemplary embodiment of the present invention, the olefin-based polymer may be prepared by a gas phase polymerization method, a solution polymerization method, a slurry polymerization method, etc. Preferably, the polymerization of the olefin-based monomer may be performed by slurry polymerization, and specifically, the polymerization of the olefin-based monomer may be performed in a slurry batch reactor.

[0130] When the olefin-based polymer is prepared by a solution polymerization method or a slurry polymerization method, examples of the solvent to be used may include C 5-12 Aliphatic hydrocarbon solvents such as pentane, hexane, heptane, nonane, decane and isomers thereof; aromatic hydrocarbon solvents such as toluene and benzene; hydrocarbon solvents substituted with chlorine atoms such as dichloromethane and chlorobenzene; and mixtures thereof, but are not limited thereto.

[0131] Embodiments of the invention

[0132] Example

[0133] Hereinafter, the present invention will be described in more detail by the following examples. However, the following examples only illustrate the present invention and do not limit the scope of the present invention.

[0134] Preparation Example

[0135] The transition metal compound of Chemical Formula 1-1 (bis[(1-butyl-3-methyl)cyclopentadienyl]zirconium dichloride) and the transition metal compound of Chemical Formula 1-2 (bis(n-butylcyclopentadienyl)zirconium dichloride) were purchased from TCI, and the transition metal compound of Chemical Formula 2-1 was prepared as follows.

[0136] Preparation of 2-(trimethylsilylmethyl)-2-propen-1-ol

[0137] By potassium carbonate (K CO ) aqueous solution (6.6M, 14.4mmol) slowly add in the solution that acetic acid 2-(trimethylsilylmethyl) allyl ester (2.69g, 14.4mmol) is dissolved in methyl alcohol (22ml).After interpolation, it is at room temperature stirred 4 hours.After stirring, water is added wherein to complete the reaction.Use ether extraction organic layer, then use magnesium sulfate (MgSO 4 ) remove remaining water.Under vacuum, remove all solvents to obtain 1.51g (72%) light milky white oily compound.

[0138] 1 H-NMR (CDCl3, 300MHz): δ4.90-4.88(m,1H),4.66(s,1H),3.97(s,2H),1.53(s,2H),0.03(s,9H).

[0139] Preparation of 2-(trimethylsilylmethyl)methanesulfonate

[0140] Methanesulfonyl chloride (1.8 g, 15.7 mmol) was slowly added to a solution of 2-(trimethylsilylmethyl)-2-propene-1-ol (1.51 g, 10.5 mmol) and triethylamine (1.91 g, 18.8 mmol) diluted with dichloromethane (30 ml) at 0° C. Thereafter, stirring was performed at 0° C. for 3 hours. A sodium bicarbonate (NaHCO ) aqueous solution was added at 0° C. to complete the reaction, and then the organic layer was separated by extraction with dichloromethane. The remaining water was removed with sodium sulfate (Na SO ), and then all solvents were removed under vacuum to obtain 1.9 g (82%) of a yellow oily compound.

[0141] 1H-NMR (CDCl3, 300MHz): δ5.03(d,1H),4.84(s,1H),4.56(s,2H),3.02(s,3H),1.60(s,2H),0.06(s,9H).

[0142] Preparation of 2-(trimethylsilylmethyl)allyl bromide

[0143] A solution in which lithium bromide was dispersed in tetrahydrofuran (15 ml) was slowly added to a solution of 2-(trimethylsilylmethyl)methanesulfonate (1.9 g, 8.54 mmol) diluted with 20 ml of tetrahydrofuran (THF) at room temperature, and then stirred at 110° C. for 4 hours. Distilled water was added at 0° C. to complete the reaction, and then the organic layer was separated by extraction with diethyl ether. The remaining water was removed with sodium sulfate (Na SO ), and then all solvents were removed under vacuum to obtain 1.12 g (65%) of a yellow oily compound.

[0144] 1 H-NMR (CDCl3, 300MHz): δ5.04(s,1H),4.74(d,1H),3.90(d,2H),1.72(d,2H),0.05(s,9H).

[0145] Preparation of [2-(cyclopentadienylmethyl)allyl]trimethylsilane

[0146] At -30 ° C, sodium cyclopentadiene (3.04 g, 6.49 mmol, 2M THF solution) was slowly added dropwise to a solution of 2-(trimethylsilylmethyl)allyl bromide (1.12 g, 5.41 mmol) diluted in tetrahydrofuran (20 ml), the temperature was slowly raised to room temperature, and stirred for 12 hours. Distilled water was added at 0 ° C to complete the reaction, and then extracted with ether to separate the organic layer. The remaining water was removed with magnesium sulfate, and then separated by column chromatography (hexane) to obtain 620 mg (60%) of a light milky white oily compound.

[0147] 1 H-NMR (CDCl3, 300MHz): δ6.42-6.02(m,4H),4.60-4.55(m,2H),3.06-2.97(m.2H),2.87-2.85(m,2H),1.54(s,2H),0.03(d,9H).

[0148] Preparation of [2-(trimethylsilylmethyl)allyl]cyclopentadienyllithium

[0149] At -30 ° C, n-butyl lithium (n-BuLi) (1.44 g, 2.93 mmol, 1.6 M hexane solution) was slowly added to a solution of [2- (cyclopentadienylmethyl) allyl] trimethylsilane (620 mg, 3.22 mmol) diluted with tetrahydrofuran (10 ml), the temperature was slowly raised to room temperature, and the mixture was stirred for 12 hours. The solvent of the reaction solution was dried under vacuum, hexane was added thereto, and the mixture was stirred for 15 minutes. The resulting solid was filtered and dried under vacuum to obtain 528 mg (83%) of a light yellow solid compound.

[0150] Preparation of Bis[(2-trimethylsilylmethylallyl)cyclopentadienyl]Hafnium Dichloride

[0151] At -30 ° C, a solution of hafnium chloride (HfCl4) (226 mg, 0.71 mmol) dispersed in toluene (2 ml) was slowly added to a solution of [(2-trimethylsilylmethyl) allyl] cyclopentadienyl lithium (280 mg, 1.41 mmol) diluted with toluene (3 ml), the temperature was slowly raised to room temperature, and stirred for 12 hours. When the reaction was complete, the reaction solution was filtered, and the solvent of the filtrate was dried under vacuum. The resulting solid was washed with hexane and dried to obtain 180 mg (41%) of a white solid compound.

[0152] 1 H-NMR (CDCl3, 300MHz): δ6.21(t,2H),6.12(t,2H),4.54(d,2H),4.44(d,1H),3.28(s,2H),1.52(s,2H),0.05(s,9H).

[0153] Preparation of Bis[(2-trimethylsilylmethylallyl)cyclopentadienyl]dimethyl Hafnium

[0154] MeMgBr (3.93 g, 11.4 mmol, 3.0 M ether solution) was slowly added to a solution of bis[(2-trimethylsilylmethylallyl)cyclopentadienyl]hafnium dichloride (2.4 g, 3.79 mmol) diluted with toluene (40 ml) at -30 ° C. The temperature was slowly raised to room temperature and stirred for 12 hours. After the reaction was completed, extraction was performed with toluene and filtration was performed. Toluene was removed under vacuum, and the mixture was washed with hexane and dried to obtain 2.08 g (93%) of a white solid compound.

[0155] Preparation Example 1

[0156] 8.71 g of a 10% toluene solution of methylaluminoxane was added to 17.9 mg of the transition metal compound of Chemical Formula 1-1 and 57.0 mg of the transition metal compound of Chemical Formula 2-1, and the solution was stirred at room temperature for 1 hour. The resulting solution after the reaction was added to 1.94 g of silica (XPO-2402), and 15 ml of toluene was further added, and stirred at 70°C for 2 hours. The supported catalyst was washed three times with 5 ml of toluene and dried under vacuum at 60°C overnight to obtain 2.80 g of a supported catalyst in powder form.

[0157] Preparation Example 2

[0158] 2.6 g of a supported catalyst was obtained in the same manner as in Preparation Example 1, except that 15.5 mg of the transition metal compound of Chemical Formula 1-2 was used instead of the transition metal compound of Chemical Formula 1-1.

[0159] Examples 1 to 8

[0160] Ethylene / 1-hexene copolymers were prepared using a slurry batch polymerization reactor in the presence of supported catalysts, each of which was obtained in Preparation Examples 1 and 2. The polymerization conditions for the examples are summarized in Table 1 below:

[0161] [Table 1]

[0162]

[0163] Comparative Examples 1 and 2

[0164] For comparison, linear low-density polyethylene M1810HN (density: 0.9180 g / cm 3 , melt index: 1.0 g / 10 min; Comparative Example 1) and M2010EN (density: 0.9200 g / cm 3 , melt index: 1.0 g / 10 min; Comparative Example 2).

[0165] Test Case

[0166] The physical properties of the olefin-based polymers of the above examples were measured by the following methods and standards. The results are shown in Tables 2 and 3 below.

[0167] (1) Density

[0168] Measured according to ASTM D1505.

[0169] (2) Melt index and melt index ratio (MFR)

[0170] The melt index was measured at 190°C under a load of 21.6 kg and 2.16 kg, respectively, according to ASTM D 1238, and the ratio (MI 21.6 / MI 2.16 ).

[0171] (3) Comonomer distribution slope (CDS)

[0172] Measured using gel permeation chromatography-FTIR (GPC-FTIR) at 170°C.

[0173] [Table 2]

[0174] unit Example 1 Example 2 Example 3 Example 4 Example 5 Melt index g / 10 minutes 0.08 0.31 0.44 1.46 1.5 MFR - 25.4 20.4 21.4 23.5 16.9 density <![CDATA[g / cm 3 ]]> 0.9204 0.9255 0.9265 0.9300 0.9250 Mw g / mol 256,087 196,819 188,490 148,642 148,898 Mw / Mn - 6.51 5.49 6.14 6.44 6.99 CDS - 1.96 1.36 1.08 1.75 1.34

[0175] [Table 3]

[0176] unit Example 6 Example 7 Example 8 Comparative Example 1 Comparative Example 2 Melt index g / 10 minutes 2.04 2.28 4.04 0.29 0.003 MFR - 17 16.1 18 20.7 403 density <![CDATA[g / cm 3 ]]> 0.9287 0.9313 0.9323 0.9270 0.9165 Mw g / mol 137,279 138,929 119,924 168,282 258,327 Mw / Mn - 5.76 5.74 5.26 2.12 3.91 CDS - 1.66 1.39 2.26 0.37 0.37

[0177] Industrial Applicability

[0178] Since the olefin-based polymer according to an exemplary embodiment of the present invention has a wide molecular weight distribution and thus excellent processability, and has a relatively large amount of short chain branches in a high molecular weight component, the olefin-based polymer has excellent mechanical strength and heat sealing properties.

Claims

1. An olefin-based polymer having (1) 0.915 g / cm 3 to 0.935g / cm 3 (2) a melt index (I) of 15 or greater measured at 190°C under a load of 21.6 kg 21.6 ) and the melt index (I 2.16 ) ratio (melt flow ratio; MFR); and (3) a comonomer distribution slope (CDS) of 1.0 or greater, as defined by the following formula 1: [Formula 1] Among them C 20 and C 80 is the comonomer content at the points where the cumulative weight fractions in the comonomer distribution are 20% and 80%, respectively, and M 20 and M 80 are the molecular weights at the points in the comonomer distribution where the cumulative weight fractions are 20% and 80%, respectively.

2. The olefin-based polymer of claim 1, wherein the olefin-based polymer has (1) 0.918 g / cm 3 to 0.932g / cm 3 (2) a density of 15 to 40; (2) an MFR of 15 to 40; and (3) a CDS of 1.0 to 3.

0.

3. The olefin-based polymer according to claim 1, wherein the olefin-based polymer is prepared by polymerizing an olefin-based monomer in the presence of a mixed catalyst, the mixed catalyst comprising: at least one first transition metal compound represented by the following Chemical Formula 1; and at least one second transition metal compound represented by the following Chemical Formula 2: [Chemical Formula 1] [Chemical Formula 2] wherein n is independently an integer from 1 to 20, M is independently titanium (Ti), zirconium (Zr), or hafnium (Hf), X is independently halogen, C 1-20 Alkyl, C 2-20 Alkenyl, C 2-20 Alkynyl, C 6-20 Aryl, C 1-20 Alkyl C 6-20 Aryl, C 6-20 Aryl C 1-20 Alkyl, C 1-20 Alkylamide, or C 6-20 Arylamide, R1 to R8 are independently hydrogen, substituted or unsubstituted C 1-20 Alkyl, substituted or unsubstituted C 2-20 Alkenyl, substituted or unsubstituted C 6-20 Aryl, substituted or unsubstituted C 1-20 Alkyl C 6-20 Aryl, substituted or unsubstituted C 6-20 Aryl C 1-20 Alkyl, substituted or unsubstituted C 1-20 Heteroalkyl, substituted or unsubstituted C 3-20 Heteroaryl, substituted or unsubstituted C 1-20 Alkylamide, substituted or unsubstituted C 6-20 Arylamide, substituted or unsubstituted C 1-20 Alkylene, or substituted or unsubstituted C 1-20 Silyl, and R9 to R 11 and R 12 to R 14 are independently substituted or unsubstituted C 1-20 Alkyl, substituted or unsubstituted C 2-20 Alkenyl, substituted or unsubstituted C 6-20 Aryl, substituted or unsubstituted C 1-20 Alkyl C 6-20 Aryl, substituted or unsubstituted C 6-20 Aryl C 1-20 Alkyl, substituted or unsubstituted C 1-20 Heteroalkyl, substituted or unsubstituted C 3-20 Heteroaryl, substituted or unsubstituted C 1-20 Alkylamide, substituted or unsubstituted C 6-20 Arylamide, substituted or unsubstituted C 1-20 Alkylene, or substituted or unsubstituted C 1-20 Silyl, but R1 to R8 can be independently connected to adjacent groups to form a substituted or unsubstituted saturated or unsaturated C 4-20 ring.

4. The olefin-based polymer according to claim 3, wherein M is zirconium or hafnium, and X is halogen or C 1-20 Alkyl, R1 to R8 are hydrogen, substituted or unsubstituted C 1-20 Alkyl, substituted or unsubstituted C 1-20 alkenyl, or substituted or unsubstituted C 6-20 Aryl, and R9 to R 11 and R 12 to R 14 are substituted or unsubstituted C 1-20 alkyl.

5. The olefin-based polymer according to claim 3, wherein the first transition metal compound is at least one of the transition metal compounds represented by the following Chemical Formulas 1-1 to 1-3, and the second transition metal compound is a transition metal compound represented by the following Chemical Formula 2-1: [Chemical Formula 2-1] Wherein Me is methyl. 6 . The olefin-based polymer according to claim 3 , wherein a molar ratio of the first transition metal compound to the second transition metal compound is in the range of 100:1 to 1:

100.

7. The olefin-based polymer according to claim 3, wherein the catalyst comprises at least one co-catalyst compound selected from the group consisting of a compound represented by the following Chemical Formula 3, a compound represented by the following Chemical Formula 4, and a compound represented by the following Chemical Formula 5: [Chemical Formula 3] [Chemical Formula 4] [Chemical Formula 5] [L-H] + [Z(A)4] - or [L] + [Z(A)4] - Where n is an integer of 2 or greater, R a Halogen atoms, C 1-20 Hydrocarbon, or halogen-substituted C 1-20 Hydrocarbon group, D is aluminum (Al) or boron (B), R b 、R c and R d are independently halogen atoms, C 1-20 Hydrocarbon, halogen-substituted C 1-20 Hydrocarbon, or C 1-20 Alkoxy, L is a neutral Lewis base or a cationic Lewis base, [LH] + and [L] + is a Bronsted acid, Z is a Group 13 element, and A is independently substituted or unsubstituted C 6-20 Aryl or substituted or unsubstituted C 1-20 alkyl. 8 . The olefin-based polymer according to claim 7 , wherein the catalyst further comprises a carrier supporting the transition metal compound, the co-catalyst compound, or both. 9 . The olefin-based polymer according to claim 8 , wherein the support comprises at least one selected from the group consisting of silica, alumina, and magnesia.

10. The olefin-based polymer according to claim 8, wherein the total amount of the mixed transition metal compound loaded on the carrier is 0.001 to 1 mmol based on 1 g of the carrier, and the total amount of the co-catalyst compound loaded on the carrier is 2 to 15 mmol based on 1 g of the carrier. 11 . The olefin-based polymer according to claim 1 , wherein the olefin-based polymer is a copolymer of an olefin-based monomer and an olefin-based comonomer.

12. The olefin-based polymer of claim 11, wherein the olefin-based monomer is ethylene, and the olefin-based comonomer is one or more selected from the group consisting of propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, 1-heptene, 1-octene, 1-decene, 1-undecene, 1-dodecene, 1-tetradecene, and 1-hexadecene. 13 . The olefin-based polymer according to claim 12 , wherein the olefin-based polymer is a linear low density polyethylene in which the olefin-based monomer is ethylene and the olefin-based comonomer is 1-hexene.

14. A method for preparing an olefin-based polymer, the method comprising: An olefin-based polymer is obtained by polymerizing an olefin-based monomer in the presence of a mixed catalyst comprising: at least one first transition metal compound represented by the following Chemical Formula 1; and at least one second transition metal compound represented by the following Chemical Formula 2, wherein the olefin-based polymer has (1) 0.915 g / cm 3 to 0.935g / cm 3 (2) a melt index (I) of 15 or greater measured at 190°C under a load of 21.6 kg 21.6 ) and the melt index (I 2.16 ) ratio (melt flow ratio; MFR); and (3) a comonomer distribution slope (CDS) of 1.0 or greater, as defined by the following formula 1: [Chemical Formula 1] [Chemical Formula 2] [Formula 1] Where n, M, X, R1 to R8 and R9 to R 14 As defined in claim 3, and C 20 、C 80 、M 20 and M 80 As defined in claim 1. 15 . The method for preparing an olefin-based polymer according to claim 14 , wherein the polymerization of the olefin-based monomer is performed by slurry polymerization.